Impact of Aquatic Physiotherapy on Arterial Pressure of Aged People - Okano Gimenes, Rafaela; Toledo Pimentel de Carvalho, Nathália; Calza Farelli, Bianca; Wetzel Pinto de Mello, Thiago (O Mundo da Saúde, 2008)
Cardiovascular diseases increase with age, and their complications are reduced by exercising. The aquatic environment is appropriate for the practice of exercises. This work aims to evaluate the variation of arterial pressure (AP) in aged people that practice aquatic group physiotherapy, in two definite periods and comparing AP rates measured in these periods. Twenty patients with more than 60 years of age, both male and female, without cognitive compromising and that did not practice regular physical activity for a year were the subjects of the study; they were submitted to an initial evaluation and to another at the end of each therapeutic session. The program of aquatic physiotherapy was applied two times a week, in 45- minute sessions, during 12 weeks, consisting of 10 minutes of heating, 20 minutes of aerobic exercises and relaxation in the 15 final minutes. Preprotocol Systolic Arterial Pressure (SAP) daily average rate in the first and last day was not significant (p = 0.3726). But after-protocol SAP average rate in the first and last day evidenced a statistically significant reduction (p = 0.0486). Diastolic Arterial Pressure (DAP) average rates in pre-protocol in the first and last day was not statistically significant (p = 0.5359), and the same applied to after-protocol average rates (p = 0.9149). We concluded, after analysis of the results, that the proposed protocol was beneficial to the group studied, based on the comparison of the first and the last day of assistance after three months of application of the protocol.